2018
DOI: 10.1055/s-0038-1641141
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis Comparing Liposomal Bupivacaine and Traditional Periarticular Injection for Pain Control after Total Knee Arthroplasty

Abstract: Liposomal bupivacaine is a novel method for pain control after total knee arthroplasty (TKA), but recent studies showed no advantage for patients undergoing TKA compared with traditional periarticular injection (PAI). The purpose of this analysis was to compare the clinical outcomes between liposomal bupivacaine treatment and traditional PAI. We retrospectively reviewed data from 16 clinical trials in published databases from their inception to June 2017. The primary outcome was postoperative Visual Analogue S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Bagsby et al [37] perform a retrospective cohort study and concluded that “liposomal bupivacaine PAI provided inferior pain control compared to the less expensive traditional PAI in a multi-modal pain control programme in patients undergoing TKA”. Interestingly, the efficacy of liposomal bupivacaine was better in the meta-analysis performed by Wang et al [9], similar in the meta-analysis conducted by Kuang et al [10], and worse in the meta-analysis performed by Sun et al [11]. Obviously, the comparison has not reached a unified recommendation.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Bagsby et al [37] perform a retrospective cohort study and concluded that “liposomal bupivacaine PAI provided inferior pain control compared to the less expensive traditional PAI in a multi-modal pain control programme in patients undergoing TKA”. Interestingly, the efficacy of liposomal bupivacaine was better in the meta-analysis performed by Wang et al [9], similar in the meta-analysis conducted by Kuang et al [10], and worse in the meta-analysis performed by Sun et al [11]. Obviously, the comparison has not reached a unified recommendation.…”
Section: Discussionmentioning
confidence: 90%
“…Liposomal bupivacaine is an updated medication from bupivacaine, which is scraped from liposomes and injected into surgical site to alleviate postoperative pain. Since the drug was approved by the FDA in 2013, a series of clinical trials [3537] and meta-analysis [911] have compared the efficacy of liposomal bupivacaine with traditional peri-articular injection (TPAI) following total joint arthroplasty (TJA). Lonner et al [35] concluded that it is an “effective mechanism to assist in early hospital discharge and rapid recovery after TJA.” Barrington et al [36] conduct a clinical trial with more than 1000 patients and demonstrated that LB showed superiority in lower pain scores and reduced length of hospital stay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the end stage of OA, total joint arthroplasty was the final choice [15,16]. Total joint arthroplasty was always associated with an increase in economic costs [17]. Preventing OA progress could relieve knee pain and decrease relevant costs.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, there have been eight meta‐analyses comparing the above three types of analgesic methods. Two of them compare the efficacy of LB with FNB following TKA.…”
Section: Introductionmentioning
confidence: 99%